MORPHOMETRIC PARAMETERS OF THE CRANIOFACIAL AREA OF ELDERLY PEOPLE WITH PARTIAL AND COMPLETE ADENTIA" - Nurov N. B; Teshaev Sh. J (International Journal of Human Computing Studies, 2020)
Currently, the problem of adentia affects the entire population of the earth, regardless of race,age, or gender, this pathology of the dentoalveolar system is formed during the development of teeth at the stage of laying. In this regard, it is very important to know all the causes that can cause primary adentia